2020
DOI: 10.1089/ped.2019.1137
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Improves Inflammation, Oxidative Stress, and Impaired Wound Healing in Atopic Dermatitis Model of Human Keratinocytes

Abstract: Background: Atopic dermatitis (AD) is a common inflammatory skin disease with complex pathogenesis. Natural flavonoids exhibit strong anti-inflammatory and antioxidant properties in many human diseases. In this study, the potential bioactive effect of quercetin, a polyphenolic plant-derived flavonoid, on the AD model of human keratinocytes was evaluated. Methods: Immortalized human HaCaT keratinocytes were treated with interleukin (IL) -4, -13, and tumor necrosis factor-a to mimic AD features in vitro. Then ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 50 publications
1
49
0
1
Order By: Relevance
“… 73 Additionally, Quercetin pre-treatment reduced oxidative stress through the generation of antioxidants within the in vitro model for AD using HaCaT cells treated with IL-4, IL-13, and TNF-α. 74 Quercetin also increased the mRNA expression of occludin and E-cadherin, while downregulating MMP1, MMP2, and MMP9 expression stimulating wound healing in stimulated HaCaT cells as well as, downregulated phosphorylation of MAPK, and NF-κB reducing inflammation. 74 …”
Section: Discussionmentioning
confidence: 95%
“… 73 Additionally, Quercetin pre-treatment reduced oxidative stress through the generation of antioxidants within the in vitro model for AD using HaCaT cells treated with IL-4, IL-13, and TNF-α. 74 Quercetin also increased the mRNA expression of occludin and E-cadherin, while downregulating MMP1, MMP2, and MMP9 expression stimulating wound healing in stimulated HaCaT cells as well as, downregulated phosphorylation of MAPK, and NF-κB reducing inflammation. 74 …”
Section: Discussionmentioning
confidence: 95%
“…is causes the substance to block the chemical pathway of some of the ways in which inflammation is produced. As a result, quercetin is able to reduce pain from arthritis, gout, rheumatism, and general inflammation, in which people usually suffer from [60]. þIt has been shown to have different aldose reductase inhibitory properties.…”
Section: Investigation Of Medicinal Properties Of Pistachio Skinmentioning
confidence: 99%
“…Several studies showed that wound healing was impaired in AD, as shown by Beken et al, in 2020, where HaCaT induced with AD-stimulating agents showed delayed wound healing [54].…”
Section: Wound-healing Activitymentioning
confidence: 99%
“…e expression of these genes is necessarily slightly increased in wound healing to facilitate cell migration. However, overexpression of these genes could actually interfere with tissue repair since it will result in excessive ECM degradation in the tissue regeneration stage [54]. Another study by Zhao et al also showed delayed wound healing in IL-4 Tg mice model for AD despite the robust keratinocyte proliferation specific to AD pathophysiology [55].…”
Section: Wound-healing Activitymentioning
confidence: 99%